Channel selection with symmetric manufacturers’ competition in multi-channel supply chains - Zhang, Yumeng (2018)
Innovative selling channels have brought about opportunities as well as challenges for upstream manufacturers. The past few years have witnessed both success and failure of manufacturers with different channel strategies. To explore the rationale of different channel strategies in different business contexts, we develop a linear demand model to analyze a manufacturer’s channel selection between two single-channel strategies (i.e., direct-channel strategy and retail-channel strategy) and a dual-channel strategy (i.e., strategy with both direct and retail channels) resting on consumers’ preference and cost levels of the differentiation between retail and direct channels, which centres the conflict in the nature of channel differentiation both in the cost side and in the market side. Specifically, we incorporate the behavior of a symmetric competitor and track down the change of the focal manufacturer’s channel preference, which has been surprisingly neglected in the literature since previous researchers mainly focus on a single manufacturer’s decision-making scenario. Comparing this new scenario with the single manufacturer’s channel selection in previous literature clarifies the effects of network positions in the same market segment and offers insights into the current intertwined business relationships in practice. Our finding shows that the channel preference is a dynamic choice depending on the channels’ operating costs and market factors of consumers’ purchasing attitude. In addition, our results show that the impacts of consumer’s channel preference can be either overestimated or underestimated in deciding the focal manufacturer’s channel selection strategy if the manufacturer considers itself as the only decision maker in the upstream. Actually, the competitor needs to compete with the manufacturer for customers, which significantly changes the focal manufacturer’s decision marking on channel strategy. Finally, we summarize the equilibria in the game between two manufacturers and show that the asymmetric channel structure cannot be a Nash equilibrium in this game.